Evaluation of a novel thermophilic nitrifying Bacillaceae species Aliibacillus thermotolerans BM62T promoting nitrogen retention in livestock manure compost. Issue 3 (4th November 2019) - Xu, Jie; Xu, Xiuhong; Han, Yue; Sheng, Siyuan; Meng, Qingxin; Wang, Zeyi; Liu, Wenyue; Di, Lubin
Abstract: Aliibacillus thermotolerans BM62 T is a novel thermophilic nitrifying bacterium, which belongings to the family Bacillaceae . A laboratory scale composting was done to evaluate the effect of adding strain BM62 T on nitrogen retention during the process of animal waste compost. During the whole composting process, the ammonia emission of the compost with BM62 T added was 29.71% lower than that of the control compost. In addition, the emission amount reduced in the warming and high temperature period accounted for 92.19% of the total emission amount reduced by the addition of strain BM62 T . In the early stage of composting (0–14 days), the ammonium content in the BM62 T ‐added compost was significantly lower than that of the control compost, while the content of nitrite and nitrate was significantly higher than that of the control compost. At the end of composting, the nitrate content in the BM62 T ‐added compost (3.25 g/kg DM) was significantly higher than that of the control compost (0.14 g/kg DM). The number of thermophilic bacteria increased by 73.07% and that of thermophilic nitrifying bacteria increased by 75.56% in the compost with BM62 T added. While the number of thermophilic bacteria increased by 29.61% and that of thermophilic nitrifying bacteria increased by 31.72% in the control compost. These results showed that BM62 T could effectively reduce the ammonia emission especially during the high temperature period of compost, which make it has good application value in livestock and poultry manure compost treatment for promoting nitrogen retention.